The role of glucagon after bariatric/metabolic surgery: much more than an “anti-insulin” hormone - Pérez-Arana, Gonzalo-Martín; Díaz-Gómez, Alfredo; Bancalero-de los Reyes, José; Gracia-Romero, Manuel; Ribelles-García, Antonio; Visiedo, Francisco; González-Domínguez, Álvaro; Almorza-Gomar, David; Prada-Oliveira, José-Arturo (Frontiers in Endocrinology, 2023)
The biological activity of glucagon has recently been proposed to both stimulate hepatic glucose production and also include a paradoxical insulinotropic effect, which could suggest a new role of glucagon in the pathophysiology type 2 diabetes mellitus (T2DM). An insulinotropic role of glucagon has been observed after bariatric/metabolic surgery that is mediated through the GLP-1 receptor on pancreatic beta cells. This effect appears to be modulated by other members of the proglucagon family, playing a key role in the beneficial effects and complications of bariatric/metabolic surgery. Glucagon serves a dual role after sleeve gastrectomy (SG) and Roux-en-Y gastric bypass (RYGB). In addition to maintaining blood glucose levels, glucagon exhibits an insulinotropic effect, suggesting that glucagon has a more complex function than simply an “anti-insulin hormone”.